Characterisation of torsional actuation in highly twisted yarns and fibres. (September 2015) - Aziz, Shazed; Naficy, Sina; Foroughi, Javad; Brown, Hugh R.; Spinks, Geoffrey M.
Abstract: Highly twisted oriented polymer fibres and carbon nanotube yarns show large scale torsional actuation from volume expansion that can be induced, for example, thermally or by electrochemical charging. When formed into spring-like coils, the torsional actuation within the fibre or yarn generates powerful tensile actuation per muscle weight. For further development of these coil actuators and for the practical application of torsional actuators, it is important to standardise methods for characterising both the torsional stroke (rotation) and torque generated. By analogy with tensile actuators, we here introduce a method to measure both the free stroke and blocked torque in a one-end-tethered fibre. In addition, the torsional actuation can be measured when operating against an externally applied torque (isotonic) and actuation against a return spring fibre (variable torque). A theoretical treatment of torsional actuation was formulated using torsion mechanics and evaluated using a commercially available highly-oriented polyamide fibre. Good agreement between experimental measurements and calculated values was obtained. The analysis allows the prediction of torsional stroke under any external loading condition based on the fundamental characteristics of the actuator: free stroke and stiffness.